Reflections on treatment of COVID-19 with traditional Chinese medicine - Luo, Hua (Chin Med, 2020)
Coronavirus disease 2019 (COVID-19) pandemic is spreading rapidly around the globe. By the establishment of an integrative system combining both traditional Chinese medicine (TCM) and western medicine, China has achieved good clinical efficacy in the prevention and control of the pandemic. The advantages of TCM in the treatment of COVID-19 include effective relief of symptoms, retarding the development from mild and moderate to severe, improvement of cure rate, reducing death rates, and promotion of rehabilitation. Besides, according to the different severity levels of individual cases, the National Health Commission of the People’s Republic of China issued treatment guidelines that provide corresponding prescriptions for patients. From the perspective of TCM, this review aims to analyze the role of a variety of TCM prescriptions in the treatment of COVID-19, focusing on the analysis of the “Three TCM prescriptions and three medicines” recommended by the Chinese authorities during the pandemic. We expect that this review will provide insights into the prevention and treatment of COVID-19 with TCM.